RANCANG BANGUN ALAT PAKAN IKAN OTOMATIS MENGGUNAKAN MIKROKONTROLER NODEMCU ESP8266 BERBASIS INTERNET OF THINGS (IOT) MENGGUNAKAN APLIKASI BLYNK STUDI KASUS : AKUARIUM RUMAHAN - Jonathan Adi Prasetyo (CV. Multi Kreasi Media, 2024)
The development of sat technology is currently growing rapidly, today's technology is no longer a compliment but has become a necessity. One of them is in the world of fish farming. Developing technology offers a wide range of automatic device options that are deliberately created for personal and group convenience. The automatic device itself offers us not have to do the activity repeatedly, but the repetitive activity has been done with the automatic device. One of them is a fish feed system based on the Internet of Things. Challenges arise when the owner is busy with his activities while required to provide fish so that the fish continue to grow properly. Therefore this research was conducted to overcome the problems that arise when the owner cannot provide feed directly or provide feed at the right time because he has other things to do. NodeMCU can be used as a tool to receive input and output of a sensor and as a device that can connect to the internet because NodeMCU is equipped with an ESP8266 chip, by adding a servo motor as a feed aid, and the Blynk application for scheduling media, then feeding can be done and scheduled remotely.